AS Business Studies - Surridge, Malcolm; Gillespie, Andrew (London : Hodder & Stoughton, 2004)
'AS Business Studies' has been written for the Advanced Subsidiary Syllabus effective from September 2000. It aims to provide students with the knowledge, understanding and examination skills essential for success in the new examination.
Previous ed.: 2000.
Includes index.
Keywords: Business; Business -- Problems, exercises, etc; Business -- Examinations -- Study guides; Business and Management